Pengaruh Numbered Head Together (NHT) Untuk Meningkatkan Pemahaman Konsep Dan Motivasi Belajar IPS Peserta Didik Kelas II Di SD Anak Saleh - Mutik Nur Fadhilah; Mohamad Nurahman (EDUCARE: Journal of Primary Education, 2021)
The learning process in the new normal is currently still undergoing a process of adaptation. Where the learning is still limited face-to-face and some others are brave. Process adaptation. This learning requires an NHT learning technique that makes it easier for class II students to understand the concept of social studies learning in the natural and artificial environment as a whole and is able to increase their motivation in learning. The research method uses a quantitative design using a non-equivalent control group design. The variables of this study consisted of independent variables and dependent variables. The population of this study were all second grade students at Anak Saleh Elementary School, while the samples were second grade students who carried out the bold learning process and second grade students who carried out offline learning processes. The data collection used in this study included interviews, questionnaires and observations. The data analysis technique is validity test and reliability test. Analysis of the data used through data coding, data transfer to a computer using prerequisite tests and hypothesis testing. The results of the research show: 1) the level of understanding of the social studies concept of class II students who study with the Numbered Head Together (NHT) learning technique is better than conventional learning techniques of 0.429 (results from the t-test) and 2) the level of motivation to learn social studies of class students II with Numbered Head Together (NHT) learning technique of 0.733 is better than conventional learning which is only 0.704. Surely this is greater than rtable = 0.361.  Keywords: NHT; Concept Understanding; Motivation to Learn Proses pembelajaran di masa new normal saat ini masih mengalami proses adaptasi. Dimana pembelajarannya masih dengan tatap muka terbatas dan sebagian lainnya daring. Adaptasi proses peralihan pembelajaran inilah dibutuhkan sebuah tekhnik pembelajaran NHT yang mempermudah peserta didik kelas II dalam memahami konsep belajar IPS dalam materi lingkungan alam dan buatan secara utuh dan mampu meningkatkan motivasinya dalam belajar. Metode penelitian menggunakan kuantitatif menggunakan desain non equeivalen control grup design. Variabel penelitian ini terdiri dari variabel bebas dan variabel terikat. Populasi penelitian ini adalah seluruh peserta didik kelas II di SD Anak Saleh, sedangkan sampelnya adalah peserta didik kelas II yang melakukan proses pembelajaran daring dan kelas II yang melakukan proses pembelajaran luring. Pengumpulan data yang digunakan dalam penelitian ini meliputi wawancara, angket dan observasi. Tehnik analisis data uji validitas dan uji reliabilitas. Analisis data yang digunakan melalui pengkodean data, pemindahan data ke komputer menggunakan uji prasyarat analisis dan uji hipotesis. Hasil penelitiannya penelitian ini menunjukkan: 1) tingkat pemahaman konsep IPS peserta didik kelas II yang belajar dengan tekhnik pembelajaran Numbered Head Together (NHT) lebih baik daripada tekhnik pembelajaran konvensional sebesar 0,429 (hasil dari uji-t) dan 2) tingkat motivasi belajar IPS peserta didik kelas II dengan tekhnik pembelajaran Numbered Head Together (NHT) sebesar 0,733 lebih baik daripada tekhnik pembelajaran konvensional yang hanya sebesar 0,704. Tentunya hal ini lebih besar daripada r tabel = 0,361. Kata Kunci: NHT; Pemahaman Konsep; Motivasi Belajar